(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nugroho Y, Soendjoto MA, Suyanto, Matatula J, Alam S, Wirabuana PYAP. 2021. Traditional medicinal plants and their utilization by local communities around Lambung Mangkurat Education Forests, South Kalimantan, Indonesia. Biodiversitas 23: 306-314. Lambung Mangkurat Education Forests (LMEF) is a unique forest area with high plant diversity, including medicinal plants. This study aimed to document the list of natural medicinal plant species in LMEF and analyze the community perceptions on utilizing them. Exploratory surveys collected data through field observation and interviews with people living in villages around LMEF. The inventory of medicinal plants was conducted by line transect method with 1,000 m long and 20 m wide. Meanwhile, indigenous communities’ description of medicinal plant utilization was explored using an interview process on fifty respondents. The results showed that 56 medicinal plant species were naturally distributed in LMEF. Most plants have habitus as trees, wherein local communities commonly use their leaves as traditional medicine. Local people generally applied the extraction process using hot water to obtain the benefit of these plants. Interestingly, more than 70% of respondents prefer traditional medicine to drugs. These findings indicated that the sustainable management of LMEF can support the vital role of forest ecosystems for people’s health.